GEBELİKDE ASTIM - TETİKKURT, Cüneyt (Cerrahpaşa Medical Journal, 2014)
Background.- Asthma is one of the most common potentially serious diseases complicating pregnancy. Epidemiological studies have shown that approximately %1-4 of pregnancies are complicated by asthma. These percentages are likely to be underestimated because in many cases the condition will be undiagnosed or not recorded. Under treatment of pregnant asthmatics owing to the adverse pharmacological effects of the drugs on the fetus is another problem. Poor control and exacerbations of asthma may result in maternal hypoxia with resultant decreases in fetal oxygen saturation causing fetal hypoxia. As a result, optimal management of asthma during pregnancy requires consideration of the altered pulmonary physiology during pregnancy, the differential diagnosis of gestational asthma, the effect of pregnancy on asthma and the potential effects of asthma on the outcome of pregnancy. The goals of treatment are to maintain normal pulmonary function, prevent exacerbations and avoid adverse effects of medications.